Culinary Arts: A Motivator Towards Community-Based Festival Attendance and Sustainability - Ibraheem Kukoyi; Abioye Adedipe; Tajudeen Yusuf; Opeyemi Ijaya (International Journal of Home Economics, Hospitality and Allied Research)
This study investigates motive factors attracting people to community-based festivals characterized by culinary activities and underscore its contribution to sustaining tourism activities in the study area. Multistage sampling technique was adopted for sample selection. Kayo-Kayo Festival in the Epe area of Lagos State was purposively selected, purposive and availability sampling technique was used to select household head and one additional adult from 25 households respectively within the host community. Convenience sampling method was further used to select 100 festivals attendees, making a total of 150 respondents and a structured close-ended questionnaire was administered for data gathering. Analysis was done through the use of simple percentages, weighted mean, standard deviation and correlation analysis. Majority (79.3%) of the respondents were attracted to community-based festival because of their interest in supporting preservation of cultural heritage (M=2.63; SD=0.85). 48.6% were highly attracted by Culinary arts competition during the festival activities (M=2.41; SD=0.87). Also, most respondents opines that the festival has positive effects on the socio-cultural (M=2.45; SD=1.33) economy (M=2.43; SD= 1.49) and environment (M=3.35; SD=132) of the host community. The study found that there is a positive correlation (r= 0.356) between culinary arts and factors that motivate festival attendance. The study concludes that culinary arts motivates peoples’ attendance at festivals and therefore recommends sustaining the inclusion of culinary activities in other community-based festivals to promote attendance for the progress of the festivals and its sustainability.